2022
DOI: 10.3233/cbm-203149
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-182-5p and microRNA-205-5p as potential biomarkers for prognostic stratification of p16-positive oropharyngeal squamous cell carcinoma

Abstract: BACKGROUND: MicroRNAs constitute promising biomarkers. OBJECTIVE: The aim was to investigate diagnostic and prognostic implications of miR-182-5p and miR-205-5p in p16-positive and p16-negative oropharyngeal squamous cell carcinomas (OPSCCs). METHODS: Expression of miR-182-5p, miR-205-5p were determined via quantitative real-time-PCR in fresh frozen tissues of 26 p16-positive, 19 p16-negative OPSCCs and 18 HPV-negative oropharyngeal controls. Associations between miRNA-expression, clinicopathological character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Again intriguingly, for HPV-induced cervical cancer just the opposite mechanism, a TGF-b/Smad4-mediated increase of miR-182 has been reported and in breast cancer TGFb was described to mediate BRCAness and PARP sensitivity by induction of miR-181, which was also reported to reduce the expression of BRCA1 and ATM (15,16). Furthermore, the long isoform of miR182 (miR182-5p) was recently suggested as associated with inferior outcome in p16+ OPSCC (17).…”
Section: Introductionmentioning
confidence: 99%
“…Again intriguingly, for HPV-induced cervical cancer just the opposite mechanism, a TGF-b/Smad4-mediated increase of miR-182 has been reported and in breast cancer TGFb was described to mediate BRCAness and PARP sensitivity by induction of miR-181, which was also reported to reduce the expression of BRCA1 and ATM (15,16). Furthermore, the long isoform of miR182 (miR182-5p) was recently suggested as associated with inferior outcome in p16+ OPSCC (17).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ncRNAs, to the best of our knowledge only miR-205 and HOTAIR have been related with head and neck (112), and oropharyngeal cancers (113), as well as with cervicovaginal lavage specimens, respectively (114). In accordance with the aforementioned studies, the establishment of a panel of biomarkers with high sensitivity and specificity would be a great molecular tool to improve the diagnosis and treatment of women with LGCLs, HGCLs and CC.…”
Section: Expression Of Circulating Biomarkers In Other Hpvrelated Can...mentioning
confidence: 56%
“…In the case of ncRNAs, to the best of our knowledge only miR-205 and HOTAIR have been related with head and neck ( 112 ), and oropharyngeal cancers ( 113 ), as well as with cervicovaginal lavage specimens, respectively ( 114 ).…”
Section: Expression Of Circulating Biomarkers In Other Hpv-related Ca...mentioning
confidence: 99%
“…Generally, miRNAs may represent novel biomarkers in HPV-positive HNSCC. House et al (49) and Weiss et al (50) have reported that miR-205-5p, miR-182-5p, and miR-133a-3p were overexpressed in HPV-positive OPSCC, and could be adapted as prognostic markers (49)(50)(51). Bersani et al and Gougousis et al (45,51) have reported that miRNAs were correlated with distant tumor metastasis, invasion, and migration, even could discriminate tumor stages (2-4 of T stages) in HPVpositive Tongue squamous cell carcinoma (TSCC) and OPSCC.…”
Section: Expression and Significance Of Mirnas In Hpv-positive Hnsccmentioning
confidence: 99%